KONSERVATISME AKUNTANSI: PERAN INVESTMENT OPPORTUNITY SET, KEPEMILIKAN MANAJERIAL, DAN DEBT COVENANT PADA EMITEN IDX-80 - Syahputra, Muhammad Ridho; Meutia, Rita; Fuadi, Raida (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2025)
The purpose of this study is to look at where IDX-80 issuers gain financial attention by analyzing the influence of investment, shareholder management, and debt packages. This research focuses on all listed firms in Indonesia for the fiscal year 2021-2023. A random selection approach was utilized to choose 34 organizations as a sample, yielding 102 respondents for this study. The researchers employed a variety of methodologies to investigate the association between factors. Secondary data were acquired from yearly reports, and the data was analyzed using through analysis and SPSS25 with multiple regression. The study found that investment growth has a beneficial impact on investment policies and debt packages. Accounting conservatism is positively impacted, at least in part, by the investment opportunity set, managerial ownership, and debt covenant. Accounting conservatism is correlated with a company's debt ratio. This occurs because firms with a large amount of debt are compelled to obey the terms of the agreements that their creditors have signed with them. As a result, businesses generally use more stringent accounting procedures to ensure they are in compliance with the agreement and avoid any infractions.